Standardized protocol for labor induction: a type I hybrid effectiveness-implementation trialResearch in context - Rebecca F. Hamm; Janice Benny; Rinad S. Beidas; Knashawn H. Morales; Sindhu K. Srinivas; Samuel Parry; Lisa D. Levine (The Lancet Regional Health. Americas)
Summary: Background: Cesarean delivery remains the most common obstetrical procedure with more than 250,000 patients in the US undergoing cesarean following labor induction annually. Here, we evaluated the impact of prospectively implementing a standardized labor induction protocol on cesarean delivery rates. Methods: This multi-site type I hybrid effectiveness-implementation study compared 2 years before (PRE) and 2 years after (POST) implementation of a standardized labor induction protocol at two hospitals within the University of Pennsylvania Health System (2018–2022). The protocol included multiple components and recommended active management of labor induction, including frequent cervical examinations, amniotomy if cervical exam ≥4 cm, and interventions for labor dystocia. The primary effectiveness outcome was cesarean delivery. Secondary effectiveness outcomes included labor length, chorioamnionitis, and maternal and neonatal morbidity. The primary implementation outcome was fidelity, defined as adherence to ≥75% of the protocol components among 8 individual components that could be evaluated discretely. All data was collected via individual chart review. Findings: 8509 patients were included (PRE: n = 4214, POST: n = 4295). Our population was of median age of 31 years interquartile range (IQR) [26–35], and 44.6% identified as Black, 40.1% as white, 6.9% as Asian, and 8.4% as other or unknown; 7.4% of the population identified as Latinx. There was no significant difference in cesarean delivery rate between the two time periods overall (PRE: 21.6% vs. POST: 21.8%, p = 0.85; adjusted relative risk (aRR) 0.99 95% confidence interval (CI) [0.90–1.09]). There were no significant differences in labor length, chorioamnionitis, or composite neonatal morbidity. Maternal morbidity decreased PRE to POST (PRE: 9.3% vs. POST: 6.5%, p < 0.001; aRR 0.67 95% CI [0.58–0.79]). POST-implementation, inductions with fidelity to ≥75% of protocol components increased (PRE: 52.4% vs. POST: 59.6%, p < 0.001), evidenced by more frequent cervical examinations, earlier dilation at amniotomy, and increased labor dystocia management. Interpretation: Despite increasing standardized induction management, no significant difference in cesarean delivery was found. Funding: NICHD K23HD102523.